2021
DOI: 10.3389/fnins.2021.704785
|View full text |Cite
|
Sign up to set email alerts
|

Early Life Adversity and Polygenic Risk for High Fasting Insulin Are Associated With Childhood Impulsivity

Abstract: While the co-morbidity between metabolic and psychiatric behaviors is well-established, the mechanisms are poorly understood, and exposure to early life adversity (ELA) is a common developmental risk factor. ELA is associated with altered insulin sensitivity and poor behavioral inhibition throughout life, which seems to contribute to the development of metabolic and psychiatric disturbances in the long term. We hypothesize that a genetic background associated with higher fasting insulin interacts with ELA to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 115 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…Dated candidate gene approaches have suggested that serotonin-related polymorphisms interact with early adversity modifying the risk for stress-related psychopathology [45]. A recent study [89] filtered the genetic markers identified in a genomewide association study (GWAS) for adult high fasting insulin levels by selecting those most highly associated with peripheral insulin levels in children, to calculate a polygenic risk score (PRS). This fasting insulin PRS interacted with early life adversity and predicted childhood impulsivity at 3 years of age in an independent cohort.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Dated candidate gene approaches have suggested that serotonin-related polymorphisms interact with early adversity modifying the risk for stress-related psychopathology [45]. A recent study [89] filtered the genetic markers identified in a genomewide association study (GWAS) for adult high fasting insulin levels by selecting those most highly associated with peripheral insulin levels in children, to calculate a polygenic risk score (PRS). This fasting insulin PRS interacted with early life adversity and predicted childhood impulsivity at 3 years of age in an independent cohort.…”
Section: )mentioning
confidence: 99%
“…This fasting insulin PRS interacted with early life adversity and predicted childhood impulsivity at 3 years of age in an independent cohort. Interestingly, the markers composing the high fasting insulin PRS are mapped into genes associated with DA D2 receptor signaling, suggesting that individual variations in insulin function are related to differential effects of childhood adversity on executive functions, via DA-related mechanisms [89]. Finally, high fasting insulin genetic markers that predict childhood impulsivity in response to adversity were also significantly enriched in the accelerated cognitive decline GWAS, which may suggest that these genes are also important for long-term effects on cognition [89].…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the biggest challenges faced by researchers studying models of disease risk prediction is to develop a methodology to accurately represent an individual’s environment in a quantitative metric. Similar to how a functional PRS can represent a restricted set of phenotype-relevant biological processes, some studies have narrowed down the environment variable to a composite score made up of clearly defined constructs [see ( 48 , 49 , 85 , 86 , 88 , 89 , 91 ) for examples]. By doing so, researchers can start investigating the interplay between genes and environments while also assessing the potential ways in which genetic and environmental effects interact ( Figure 2D ).…”
Section: From Genetics To Functional Genomics: Prs Methodologies That...mentioning
confidence: 99%
“…Essentially, SNPs with p values below an established threshold will keep the original estimate of their effect size, while SNPs with higher p values are excluded from the PRS, shrinking their effect sizes to 0. This process can be carried out iteratively, using a range of p- value thresholds, with the resulting PRSs tested for an association with the target trait in a test sample, determining the optimal p value in a forward selection method ( 48 , 49 ). Other methods for PRS calculation are based on Bayesian frameworks in which the shrinkage of all SNPs is based on a prior distribution specification [for more details, see ( 50 , 51 )].…”
Section: Aggregating Gwas-derived Signals Into Prss: a Proxy For Gene...mentioning
confidence: 99%